Is examining children and adolescents with autism spectrum disorders a challenge?—Measurement of Stress Appraisal (SAM) in German dentists with key expertise in paediatric dentistry - Daniela Reis; Oliver Fricke; Andreas G. Schulte; Peter Schmidt (PLoS ONE, 2022)
Objectives This questionnaire-based validation study investigated if the dental examination of children and adolescents with autism spectrum disorder is viewed by dentists with key expertise in paediatric dentistry as a challenge or a threat in terms of transactional stress theory. The Stress Appraisal Measure (SAM) was used for this purpose and it‘s feasibility and validity was examined as a first part of a multi-stage process for validation in dentistry with a sample of German dentists. It has hardly been investigated how the treatment of children and adolescents with a disorder from the autism spectrum is perceived by dentists. Methods An online-based survey (39 questions) plus the SAM as an add-on as well as a preceding short story of imagination on the topic (appointment for a dental check-up in a special school) were developed. Via e-mail members of the German Society of Paediatric Dentistry (DGKiZ) received a link which enabled interested members to participate. The majority of the members of the DGKiZ have additional qualifications in the treatment of children and adolescents and further training in the area of special needs care in dentistry. The data analysis was based on the SAM and its subscales. Results Out of the 1.725 members of DGKiZ 92 participants (11 male, 81 female) fully completed the questionnaire and the SAM. All in all the dentists rated their own psychological and physical stress in course of treating children and adolescents with a disorder from the autism spectrum between less and partly stressful. Although the structure of the SAM could not be fully mapped by means of a factor analysis, the different ratings "challenge" or "threat" could be comprehensibly evaluated after reading the story. The participants rated the situation from the story in general as challenging but not as threatening. Intercorrelations between the subscales of the SAM (e.g threat and centrality) of r = .56 showed that the scales are not clearly independent of one another. According to the transactional stress model, the SAM bases on, stress (perceived stressfulness) arises from appraisal processes (e.g. threat, controllable-by-self) that bring about a comparison between the requirements for the described situation and one’s own possibilities in terms of a person-environment-fit. In the hierarchical regression a variance of R2 = .48 could be explained with all six subscales (appraisal processes) to predict perceived stressfulness of the SAM within a sample of dentists. Conclusions Due to the response rate the results of the SAM are not representative for all German dentists, but it offers an insight into topics of special needs dentistry in Germany that have not yet been examined. Overall, the feasibility and validity of the SAM in the context of mapping cognitive appraisal processes and stress could be confirmed. Taking into account the result that the treatment of children and adolescents with autism spectrum disorder is seen as a challenge, it is concluded that there is a need to improve the education of dental students and graduated dentists in Germany in the field of special needs dentistry.